Capacity limits in visual short-term memory for local orientations - Delvenne, J; Braithwaite, J; Riddoch, M; Humphreys, G (2002)
We used a change detection paradigm to assess the effect of spatial configuration on visual short-term memory (VSTM) capacity for single features such as orientation or texture of line elements, with the items either being presented alone or surrounded by circles. Circles were assumed to suppress the global configuration made by the stimuli in a display. We demonstrated that when the support of configural information was minimized (by the addition of circles), VSTM capacity was selectively disrupted for line orientation, with this disruptive effect increasing at the larger display sizes. In contrast, we found capacity limits on memory for line texture irrespective of whether circles were presented to disrupt the coding of lines into a more global configuration. We conclude from these observations that the relational information of individual visual items, based on global spatial configuration, is stored in VSTM and may, in some cases, increase the capacity of VSTM. We discuss the results in terms of the representation of global and local properties of forms in VSTM.